"Metabolically healthy" obesity: Prevalence, clinical features and association with myocardial ischaemia. Issue 3 (May 2017) - De Lorenzo, Andrea; Glerian, Leticia; Amaral, Ana Carolina; Reis, Thiago B.; Lima, Ronaldo S.L.
Summary: Objective: To evaluate the prevalence of the "metabolically healthy" (MH) or "metabolically unhealthy" (MU) obesity phenotypes and their association with cardiorespiratory fitness and inducible myocardial ischaemia. Methods: Individuals without known coronary artery disease undergoing myocardial perfusion single-photon emission computed tomography (MPS) were studied. Those without dyslipidemia, hypertension, or diabetes were considered MH, and when ≥1 of these was present, MU status was considered present. Summed stress and difference perfusion scores (SSS and SDS, respectively) were calculated; a SDS >1 defined ischaemic MPS. Results: MH patients were 35.0% of the nonobese population and 23.5% of the obese ( p < 0.001). The prevalence of ischaemia was not significantly different between MH patients with obesity or MH patients without obesity (10.9% vs 9.1%, p = 0.3), except for patients with body mass index ≥40 kg/m 2 (21.9%). MH obese patients were less frequently able to exercise and had lower exercise capacity than the nonobese patients. Conclusions: The prevalence of myocardial ischaemia was not significantly different between MH obese or nonobese individuals, supporting the concept of the "metabolically healthy obesity". However, there are other factors involved, such as the ability to exercise, that influence the risk of myocardial ischaemia, limiting the "safety" of that obesity phenotype.